Non-thermal approach to Listeria monocytogenes inactivation in milk: The combined effect of high pressure, pediocin PA-1 and bacteriophage P100. (April 2020) - Komora, Norton; Maciel, Cláudia; Pinto, Carlos A.; Ferreira, Vânia; Brandão, Teresa R.S.; Saraiva, Jorge M.A.; Castro, Sónia Marília; Teixeira, Paula
Abstract: Non-thermal food processing and replacement of chemical additives by natural antimicrobials are promising trends in the food industry. The objective of the present work was to evaluate the effect of a process which combines mild high hydrostatic pressure – HHP (200 and 300 MPa, 5 min, 10 °C), phage Listex™ P100 and the bacteriocin pediocin PA-1 as a new non-thermal process for destruction of Listeria monocytogenes (10 4  CFU mL −1 or 10 7  CFU mL −1 ) in milk. For inoculum levels of 10 4  CFU mL −1, HHP combined with phage P100 eliminated L. monocytogenes immediately after pressurization. When L. monocytogenes was inoculated at levels of 10 7  CFU mL −1, a synergistic effect between phage P100, pediocin PA-1 and HHP (300 MPa) on the inactivation of L. monocytogenes was observed during storage of milk at 4 °C. For non-pressure treated samples inoculated with phage or pediocin or both, L. monocytogenes counts decreased immediately after biocontrol application, but regrowth was observed in a few samples during storage. Phage particles were stable during refrigerated storage for seven days while pediocin PA-1 remained stable only during three days. Further studies will have to be performed to validate the findings of this work in specific applications (e.g. production of raw milk cheese). Highlights: Synergistic effect between phage P100, pediocin PA-1 and high pressure was demonstrated. Listeria monocytogenes (10 4  CFU mL −1 ) eliminated in milk by the pressure-phage system, being comparable to HTST pasteurization. The synergistic system (pressure-phage-pediocin) prevented L. monocytogenes regrowth during refrigerated storage. Listeria monocytogenes regrowth was not prevented when hurdles were applied individually. Phage particles were stable in milk during storage at 4 °C.